High-temperature-resistant low-reflective laser radar shading film and preparation method thereof
Patent Information
- Application Number
- CN202611399733.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本发明的目的在于提供一种耐高温低反射激光雷达遮光膜及制备方法,用于解决现有技术中没有通过对油墨层和炭黑的结构进一步改进,以解决遮光膜的耐高温性不足、红外反射率高和涂层高温相分离的技术问题
1、本发明采用聚酰亚胺薄膜作为基材,具有长期耐温,短期可耐受300℃不收缩烧毁,满足激光雷达模组的回流焊接工艺,隔热油墨涂层以环氧聚酯接枝共聚物为成膜物使玻璃化转变温度提高,引入近红外吸收剂在905nm和1550nm产生特征吸收,填补了碳黑在近红外区域吸收能力下降的不足,微纳粗糙层采用相同树脂体系使两层涂层热膨胀系数匹配避免了高温下层间应力不匹配导致的剥离、开裂的问题,通过喷涂固化制得微米级的几何起伏,散射光进入邻近的光陷阱孔隙后被孔隙内壁反复反射吸收,使红外反射率降至极低水平,改性消光炭黑的中空结构结合气相二氧化硅的纳米粗糙度形成多重光陷阱结构进一步压制表面反射,使制得的遮光膜具有优异的低反射率。
Smart Images

Figure CN122898014A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of light-shielding film technology, specifically relating to a high-temperature resistant, low-reflection lidar light-shielding film and its preparation method. Background Technology
[0002] LiDAR (Light Detection and Ranging) is a core sensor for autonomous driving, robot navigation, and environmental perception. In its internal optical system, non-imaging light rays undergo multiple reflections at the inner wall of the lens barrel, the lens edge, and around the sensor module, directly leading to a decrease in signal-to-noise ratio and a shortened detection range. Radar shielding films are functional composite films that visually present a pure black appearance to conceal internal radar components while absorbing visible light and suppressing stray light reflection. Existing radar shielding films mostly use carbon black, black pigments, metal oxides, black resin coatings, or composite films for light shielding. However, existing PET-based shielding films typically only withstand temperatures of 120-150°C, easily failing under the high temperatures of reflow soldering, and insufficient blackness of the screen-printed ink leads to residual reflection. Therefore, how to provide a shielding film suitable for radar photoelectric detection modules that maintains high light shielding performance, low transmittance, and near-infrared low reflectivity while also possessing good resistance to the high temperatures of reflow soldering is a pressing technical problem to be solved in this field.
[0003] Chinese invention patent CN119861478B discloses a lens shading film, its preparation method, and its application. The lens shading film provided by this invention includes a light-absorbing layer, a reflective layer, and an insulating layer stacked sequentially. The light-absorbing layer is in contact with the lens substrate. The material of the light-absorbing layer includes chromium and / or titanium; the material of the reflective layer includes aluminum and / or silver; and the material of the insulating layer includes silicon dioxide and / or silicon nitride. This invention significantly improves the light-shielding performance of the shading film through the synergistic effect of the light-absorbing and reflective layers. Simultaneously, the lens shading film provided by this invention has good uniformity, thereby ensuring that the optical performance of the lens is not affected. In summary, the lens shading film provided by this invention has a dense and uniform coating, achieving an OD2 greater than 2, and an average transmittance of less than 0.5% in the visible light range. However, existing technologies lack further improvements to the structure of the ink layer and carbon black to address the technical problems of insufficient high-temperature resistance, high infrared reflectivity, and high-temperature phase separation of the coating. Summary of the Invention
[0004] The purpose of this invention is to provide a high-temperature resistant, low-reflection lidar light-shielding film and its preparation method, which solves the technical problems of insufficient high-temperature resistance, high infrared reflectivity, and high-temperature phase separation of the coating in the prior art by not further improving the structure of the ink layer and carbon black.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A high-temperature resistant, low-reflection lidar light-shielding film comprises, from bottom to top, a substrate layer, a heat-insulating ink coating, and a micro-nano roughening layer; The substrate layer is a polyimide film with a thickness of 20~100μm; The heat-insulating ink coating is prepared from the following raw materials in parts by weight: 100 parts epoxy polyester graft copolymer, 10-15 parts ultrafine carbon black, 3-8 parts near-infrared absorber, 1-3 parts dispersant, 0.5-1.5 parts curing accelerator, 3-6 parts latent curing agent and 50-80 parts organic solvent; The micro-nano roughened layer is prepared from the following raw materials in parts by weight: 20-30 parts epoxy polyester graft copolymer, 5-8 parts modified matte carbon black, 3-5 parts fumed silica, 1-2 parts latent curing agent, 0.1-0.3 parts curing accelerator and 30-50 parts organic solvent.
[0006] The near-infrared absorber is at least one of phthalocyanine near-infrared absorbing dyes or diimine near-infrared absorbers.
[0007] The latent curing agent is dicyandiamide, and the curing accelerator is 2-methylimidazole.
[0008] The organic solvent is an organic solvent prepared by mixing butanone, cyclohexanone and propylene glycol methyl ether acetate in a volume ratio of 4~6:2~4:1~3.
[0009] The ultrafine carbon black has an average particle size of 20-30 nm and an oil absorption value of 90-100 mL / 100 g.
[0010] The preparation method of the modified matte carbon black includes the following steps: S11. Add ethanol and deionized water to a stirred tank, add ammonia and tetraethyl orthosilicate under stirring to prepare a suspension, then add resorcinol and 37wt% formaldehyde, heat to hydrothermal reaction, centrifuge and filter to collect the solid, wash with deionized water and ethanol in sequence, dry to obtain carbon source precursor. S12. The carbon source precursor is added to a tube furnace and carbonized in a nitrogen atmosphere. After cooling to room temperature, it is added to an 80-90 g / L sodium hydroxide aqueous solution to etch away silicon dioxide. The solid is collected by filtration, washed with deionized water and ethanol in sequence, and dried to obtain hollow carbon spheres. S13. Hollow carbon spheres are added to deionized water, zinc acetate, malic acid and isopropanol are added and stirred, 40 g / L sodium hydroxide aqueous solution is added, the mixture is heated and reacted, the solid is collected by filtration, washed with deionized water, dried, annealed and cooled to room temperature to obtain modified matte carbon black.
[0011] Preferably, the ratio of ethanol, deionized water, ammonia, tetraethyl orthosilicate, resorcinol, and 37wt% formaldehyde in S11 is (150~160) mL : (30~40) mL : (5~6) mL : (10~12) mL : (0.8~1.3) g : (1.2~1.8) mL. The mixture is stirred at 500~800 rpm for 60~120 min at 30~40℃, heated to 50~60℃ and reacted for 12~24 h. The mixture is then centrifuged at 8000~10000 rpm for 5~10 min and dried at 50~60℃ for 6~12 h.
[0012] Preferably, in step S12, the temperature is increased to 700-800℃ at a heating rate of 3-5℃ / min for carbonization for 2-4 hours, followed by etching with sodium hydroxide aqueous solution for 36-48 hours, and drying at 50-60℃ for 6-12 hours.
[0013] Preferably, the ratio of hollow carbon spheres, zinc acetate, malic acid, isopropanol, deionized water, and sodium hydroxide aqueous solution in S13 is (3~6) g : (3.5~3.8) g : (1~1.5) g : (30~40) mL : (160~170) mL : (10~12) mL. The mixture is heated to 115~120℃ for hydrothermal reaction for 4~6 h, dried at 50~60℃ for 6~12 h, and annealed at 350~400℃ for 1~2 h at a heating rate of 2~3℃ / min.
[0014] The preparation method of the epoxy polyester graft copolymer includes the following steps: S21. Neopentyl glycol, 1,3-propanediol and trimethylolpropane are added to a reaction vessel and heated and stirred. Terephthalic acid and 1,4-cyclohexanedicarboxylic acid are added under a nitrogen atmosphere. Toluenesulfonic acid is added and heated to esterify. The reaction is continued until no more water is distilled off. Vacuum polycondensation is carried out. Trimeric trioxide is added after cooling. The reaction is maintained at the temperature. The acid value is tested. The material is discharged after cooling to obtain carboxyl-terminated polyester resin. S22. Epoxy resin and carboxyl-terminated polyester resin are added to a reactor, heated and stirred to mix, triphenylphosphine is added, and the mixture is heated and reacted in a nitrogen atmosphere. The acid value is detected, the mixture is cooled and discharged to obtain an epoxy polyester graft copolymer.
[0015] Preferably, the mass ratio of neopentyl glycol, 1,3-propanediol, trimethylolpropane, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, toluenesulfonic acid, and trimellitic anhydride in S21 is 18~22:3~5:1~1.5:25~30:3~5:0.1~0.3:6~10. The mixture is heated to 100~130℃ and stirred at 100~300 rpm for 10~30 minutes. Esterification was carried out at 180~220℃ for 4~6 hours, then the temperature was raised to 240~265℃ for 2~4 hours. The vacuum degree was reduced to -0.09~-0.1MPa, and polycondensation was carried out at 210~215℃ for 1~4 hours. The temperature was lowered to 200~205℃, trimellitic anhydride was added, and the reaction was maintained at 200~220℃ for 30~60 minutes. The acid value was measured to be 30~60mgKOH / g, and the temperature was lowered to 180~190℃ for discharge.
[0016] Preferably, the epoxy resin in S22 is any one of E-44, E-42, and E-51, and the mass ratio of epoxy resin, carboxyl-terminated polyester resin, and triphenylphosphine is 30~40:60~70:0.1~0.5. The mixture is heated to 110~130℃ and stirred at 80~100 rpm for 20~30 min, then heated to 160~200℃ and reacted for 2~4 h. The reaction ends when the acid value is less than 5 mg KOH / g, and the mixture is cooled to below 100℃ before being discharged.
[0017] A method for preparing a high-temperature resistant, low-reflection lidar light-shielding film includes the following steps: S1. Epoxy polyester graft copolymer, ultrafine carbon black, organic solvent, near-infrared absorber and dispersant are added to a high-speed disperser and stirred and dispersed. Then, they are added to a grinding mill and ground. After adding curing agent and curing accelerator, they are stirred and mixed at low speed. Vacuum degassing is performed to obtain ink. S2. The ink is slit-extruded and coated onto the surface of the substrate layer, and then heated and dried in stages to obtain a heat-insulating ink coating. S3. Epoxy polyester graft copolymer, modified matte carbon black, fumed silica and organic solvent are added to a high-speed disperser and stirred and dispersed. Latent curing agent and curing accelerator are added and stirred at low speed to obtain a spray coating. The spray coating is sprayed onto the surface of the heat insulation ink coating and heated and cured to obtain a micro-nano rough layer. S4. Cool the cured light-shielding film to room temperature, roll it up, cure it, cut and package it to obtain a high-temperature resistant, low-reflection lidar light-shielding film.
[0018] Preferably, in step S1, the particles are dispersed at a speed of 1500~2500 rpm for 20~30 min, ground to a fineness of less than 5 μm, stirred at a low speed of 500~800 rpm for 20~30 min, and degassed under a vacuum of -0.08~-0.1 MPa for 20~40 min.
[0019] Preferably, in step S2, the coating speed is 10~50m / min, the coating thickness is 15~60μm, the temperature is raised to 75~85℃ for volatilization and drying for 60~180s, the temperature is raised to 115~125℃ for pre-curing for 60~180s, and finally the temperature is raised to 180~200℃ for cross-linking and curing for 60~300s.
[0020] Preferably, in step S3, the mixture is dispersed at 1500-2500 rpm for 20-30 min, stirred at 500-800 rpm for 20-30 min, degassed under a vacuum of -0.08 to -0.1 MPa for 20-40 min, and then sprayed with air at a nozzle diameter of 1.5-2.5 mm, a spraying pressure of 0.3-0.5 MPa, a spraying distance of 15-25 cm, and a gun speed of 0.5-1.0 m / s. Two to three coats are applied, each with a thickness of 3-5 μm. The interval between coats is as follows: flash drying at 60-65℃ for 30-60 s, evaporation drying at 75-85℃ for 60-120 s, pre-curing at 115-125℃ for 60-120 s, and finally cross-linking curing at 180-200℃ for 60-200 s.
[0021] Preferably, in step S4, the winding is performed at a rate of 20-50 m / min, and the product is cured at 40-50°C for 24-48 hours.
[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. This invention uses polyimide film as the substrate, which has long-term temperature resistance and can withstand 300℃ without shrinkage and burning in the short term, meeting the reflow soldering process of lidar modules. The heat-insulating ink coating uses epoxy polyester graft copolymer as the film-forming material to increase the glass transition temperature. Near-infrared absorbers are introduced to produce characteristic absorption at 905nm and 1550nm, which fills the gap in the absorption capacity of carbon black in the near-infrared region. The micro-nano rough layer uses the same resin system to match the thermal expansion coefficients of the two coatings, avoiding the peeling and cracking problems caused by interlayer stress mismatch at high temperatures. Micron-level geometric undulations are obtained by spraying and curing. After the scattered light enters the adjacent light trap pores, it is repeatedly reflected and absorbed by the inner wall of the pores, reducing the infrared reflectivity to an extremely low level. The hollow structure of modified matte carbon black combined with the nano-roughness of fumed silica forms a multi-light trap structure to further suppress surface reflection, so that the resulting light-shielding film has excellent low reflectivity.
[0023] 2. This invention utilizes pentylene glycol, 1,3-propanediol, trimethylolpropane, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid esterification polymerization. Carboxyl groups are introduced at the polyester chain ends via trimellitic anhydride deblocking, resulting in a carboxyl-terminated polyester resin. This resin is then grafted with epoxy resin to obtain an epoxy-polyester graft copolymer. The high proportion of rigid aromatic ring structures such as terephthalic acid and 1,4-cyclohexanedicarboxylic acid imparts high intrinsic rigidity to the polyester resin, increasing its glass transition temperature. The grafting of epoxy resin and polyester carboxyl groups forms a uniform single-phase system, rather than a physically blended two-phase separation system. Phase separation does not occur at high temperatures, improving the heat resistance of the light-shielding film. Under conditions of 260℃ × 30 min, the film surface shows no shrinkage, blistering, or cracking.
[0024] 3. This invention uses silica generated by the hydrolysis of tetraethyl orthosilicate as a template, encapsulates and carbonizes it with formaldehyde resin, and then removes the template with sodium hydroxide to prepare hollow carbon spheres. Nano-zinc oxide is deposited on the surface of the carbon spheres through a hydrothermal reaction. Nano-zinc oxide has good anti-reflection properties in the visible light band. By loading nano-zinc oxide particles onto the surface of the hollow carbon spheres, the optical path of incident light acting on the carbon black surface can be increased, effectively increasing the absorption cross-sectional area of the functional filler, increasing the probability of incident light being absorbed by the carbon black, and further improving the light absorption performance of the carbon spheres. This allows the incident light to undergo multiple reflections within the pores, thereby effectively enhancing light absorption and achieving synergistic enhancement of stray light absorption through absorption and scattering. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 A schematic diagram of the hierarchical structure of the present invention is shown; Figure reference numerals: 1. Substrate layer, 2. Heat-insulating ink coating, 3. Micro-nano roughening layer. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] The dispersant involved in this invention is of type BYK-163, and the fumed silica is of type VK-SP15G, with an average particle size of 30 nm and a specific surface area of 200 m². 2 / g, the ultrafine carbon black is Cabot Black Pearls® 1300, with an average particle size of 20nm and an oil absorption value of 100mL / 100g; the curing accelerator is GLOC-500.
[0029] Example 1: A high-temperature resistant, low-reflection lidar light-shielding film of this embodiment includes, from bottom to top, a substrate layer 1, a heat-insulating ink coating 2, and a micro-nano roughening layer 3. The substrate layer is a polyimide film with a thickness of 25μm; The heat-insulating ink coating is prepared from the following raw materials: 100g epoxy polyester graft copolymer, 12g ultrafine carbon black, 5g near-infrared absorber, 2g dispersant, 1g curing accelerator, 4g latent curing agent and 60g organic solvent. The micro-nano roughened layer is prepared from the following raw materials in parts by weight: 25g epoxy polyester graft copolymer, 8g modified matte carbon black, 4g fumed silica, 1g latent curing agent, 0.3g curing accelerator and 50g organic solvent.
[0030] The near-infrared absorber is a phthalocyanine-based near-infrared absorbing dye, TIR-915.
[0031] The latent curing agent is dicyandiamide, and the curing accelerator is 2-methylimidazole.
[0032] The organic solvent is an organic solvent prepared by mixing butanone, cyclohexanone and propylene glycol methyl ether acetate in a volume ratio of 5:3:2.
[0033] The method for preparing modified matte carbon black in this embodiment includes the following steps: S11. Add 160 mL of ethanol and 40 mL of deionized water to a stirred tank. Add 6 mL of ammonia and 12 mL of tetraethyl orthosilicate while stirring. Stir at 800 rpm for 120 min at 40 °C to obtain a suspension. Add 1.3 g of resorcinol and 1.8 mL of 37 wt% formaldehyde. Heat to 60 °C and react for 24 h. After the reaction is complete, centrifuge at 10000 rpm for 10 min to collect the solid. Wash with deionized water and ethanol in sequence. Dry at 60 °C for 12 h to obtain the carbon source precursor. S12. The carbon source precursor is added to a tube furnace and heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere. The carbonization is carried out at 800°C for 4 hours. After carbonization, the carbonization product is cooled to room temperature in a nitrogen atmosphere. The carbonized product is then added to 500 mL of a 90 g / L sodium hydroxide aqueous solution for etching for 48 hours to remove silicon dioxide. The solid is collected by filtration, washed with deionized water and ethanol in sequence, and dried at 60°C for 12 hours to obtain hollow carbon spheres. S13. Weigh 6g of hollow carbon spheres and add them to 170mL of deionized water. Add 3.8g of zinc acetate, 1.5g of malic acid and 40mL of isopropanol and stir to mix. Then add 12mL of sodium hydroxide aqueous solution with a concentration of 40g / L. Transfer the mixture to a closed hydrothermal reactor and heat it to 120℃ for hydrothermal reaction for 6h. After the reaction is completed, cool it to room temperature, filter and collect the solid, wash it with deionized water, dry it at 60℃ for 12h, and then heat the obtained solid to 400℃ at a heating rate of 3℃ / min. Anneal it at 400℃ for 2h and cool it to room temperature to obtain modified matte carbon black.
[0034] The preparation method of the epoxy polyester graft copolymer in this embodiment includes the following steps: S21. Add 21g neopentyl glycol, 3.5g 1,3-propanediol and 1.1g trimethylolpropane to a reaction vessel and heat to 125℃. Stir and mix at 250rpm for 15min. Add 29g terephthalic acid and 3.5g 1,4-cyclohexanedicarboxylic acid under a nitrogen atmosphere. Add 0.25g toluenesulfonic acid to catalyze the reaction. Heat to 210℃ and esterify for 4.5h. Then heat to 260℃ and esterify for another 2.5h. React until no more water is distilled off. Evacuate to -0.098MPa and polycondense at 211℃ for 2h. Cool to 204℃ and add 9g trimellitic anhydride. Keep the reaction at 205℃ for 50min. The acid value is 52mgKOH / g. Cool to 188℃ and discharge to obtain carboxyl-terminated polyester resin. S22. Add 38g of epoxy resin E-42 and 62g of carboxyl-terminated polyester resin to a reactor, heat to 125℃ and stir at 95rpm for 22min. Add 0.4g of triphenylphosphine, heat to 190℃ in a nitrogen atmosphere and react for 2.5h. The reaction ends when the acid value is 3.2mgKOH / g. Cool to 95℃ and discharge to obtain epoxy polyester graft copolymer.
[0035] The method for preparing a high-temperature resistant, low-reflection lidar light-shielding film according to this embodiment includes the following steps: S1. Epoxy polyester graft copolymer, ultrafine carbon black, organic solvent, near-infrared absorber and dispersant are added to a high-speed disperser and dispersed at 1500 rpm for 20 min. Then, the mixture is added to a grinder until the fineness is less than 5 μm. After adding curing agent and curing accelerator, the mixture is stirred at 500 rpm for 20 min. Finally, the mixture is degassed under a vacuum of -0.08 MPa for 20 min to obtain the ink. S2. The ink is slit extruded and coated onto the surface of the substrate layer at a coating speed of 30m / min and a coating thickness of 30μm. The temperature is raised to 80℃ for evaporation and drying for 180s, then raised to 120℃ for pre-curing for 180s, and finally raised to 190℃ for cross-linking and curing for 300s to obtain the heat-insulating ink coating. S3. Epoxy polyester graft copolymer, modified matte carbon black, fumed silica and organic solvent are added to a high-speed disperser and dispersed at 1500 rpm for 20 min. Latent curing agent and curing accelerator are added and stirred at low speed at 500 rpm for 20 min to obtain a spray coating. The spray coating is applied to the surface of the heat-insulating ink coating by air spraying. The spray gun nozzle diameter is 2.5 mm, the spraying pressure is 0.4 MPa, the spraying distance is 20 cm, the gun speed is 0.6 m / s, and three coats are applied. The thickness of each coat is 3 μm. The spraying interval is as follows: heat up to 60℃ for flash evaporation for 60 s, heat up to 80℃ for volatilization and drying for 120 s, heat up to 120℃ for pre-curing for 120 s, and finally heat up to 190℃ for cross-linking and curing for 180 s. Cool to room temperature to obtain a micro-nano rough layer. S4. Cool the cured light-shielding film to room temperature, roll it up at a speed of 50 m / min, cure it at 50℃ for 48 h, and then cut and package it to obtain a high-temperature resistant, low-reflection lidar light-shielding film.
[0036] Example 2: A high-temperature resistant, low-reflection lidar light-shielding film of this example includes, from bottom to top, a substrate layer, a heat-insulating ink coating, and a micro-nano roughening layer. The substrate layer is a polyimide film with a thickness of 50 μm; The heat-insulating ink coating is prepared from the following raw materials: 100g epoxy polyester graft copolymer, 10g ultrafine carbon black, 3g near-infrared absorber, 1.5g dispersant, 0.5g curing accelerator, 6g latent curing agent and 50g organic solvent; The micro-nano roughened layer is prepared from the following raw materials in parts by weight: 20g epoxy polyester graft copolymer, 5g modified matte carbon black, 3g fumed silica, 1g latent curing agent, 0.1g curing accelerator and 30g organic solvent.
[0037] The near-infrared absorber is a diimine-based near-infrared absorber, CIR-1080.
[0038] The latent curing agent is dicyandiamide, and the curing accelerator is 2-methylimidazole.
[0039] The organic solvent is an organic solvent prepared by mixing butanone, cyclohexanone and propylene glycol methyl ether acetate in a volume ratio of 4:2:1.
[0040] The method for preparing modified matte carbon black in this embodiment includes the following steps: S11. Add 150 mL of ethanol and 30 mL of deionized water to a stirred tank. Add 5 mL of ammonia and 10 mL of tetraethyl orthosilicate while stirring. Stir at 30°C and 500 rpm for 60 min to obtain a suspension. Add 0.8 g of resorcinol and 1.2 mL of 37 wt% formaldehyde. Heat to 50°C and react for 12 h. After the reaction is complete, centrifuge at 8000 rpm for 5 min to collect the solid. Wash with deionized water and ethanol in sequence. Dry at 50°C for 6 h to obtain the carbon source precursor. S12. The carbon source precursor is added to a tube furnace and heated to 700°C at a heating rate of 3°C / min in a nitrogen atmosphere. The carbonization is carried out at 700°C for 2 hours. After carbonization, the carbonization product is cooled to room temperature in a nitrogen atmosphere. The carbonized product is then added to 500 mL of an 80 g / L sodium hydroxide aqueous solution for etching for 36 hours to remove silicon dioxide. The solid is collected by filtration, washed with deionized water and ethanol in sequence, and dried at 50°C for 6 hours to obtain hollow carbon spheres. S13. Weigh 3g of hollow carbon spheres and add them to 160mL of deionized water. Add 3.5g of zinc acetate, 1g of malic acid and 30mL of isopropanol and stir to mix. Then add 10mL of sodium hydroxide aqueous solution with a concentration of 40g / L. Transfer the mixture to a closed hydrothermal reactor and heat it to 115℃ for hydrothermal reaction for 4h. After the reaction is completed, cool it to room temperature, filter and collect the solid, wash it with deionized water, dry it at 50℃ for 6h, and then heat the obtained solid to 350℃ at a heating rate of 2℃ / min. Anneal it at 350℃ for 1h and cool it to room temperature to obtain modified matte carbon black.
[0041] The preparation method of the epoxy polyester graft copolymer in this embodiment includes the following steps: S21. Add 20g neopentyl glycol, 4g 1,3-propanediol and 1.2g trimethylolpropane to a reaction vessel and heat to 115℃. Stir and mix at 200rpm for 20min. Add 28g terephthalic acid and 4g 1,4-cyclohexanedicarboxylic acid under a nitrogen atmosphere. Add 0.2g toluenesulfonic acid to catalyze the reaction. Heat to 200℃ for esterification for 5h. Then heat to 250℃ for esterification for 3h. React until no more water is distilled off. Evacuate to -0.095MPa and polycondense at 212℃ for 2.5h. Cool to 203℃ and add 8g trimellitic anhydride. Keep the reaction at 210℃ for 45min. The acid value is 45mgKOH / g. Cool to 185℃ and discharge to obtain carboxyl-terminated polyester resin. S22. Add 35g of epoxy resin E-44 and 65g of carboxyl-terminated polyester resin to a reactor, heat to 120℃ and stir at 90rpm for 25min, add 0.3g of triphenylphosphine, heat to 180℃ in a nitrogen atmosphere and react for 3h. When the acid value is 3mgKOH / g, the reaction ends, cool to 80℃ and discharge to obtain epoxy polyester graft copolymer.
[0042] The method for preparing a high-temperature resistant, low-reflection lidar light-shielding film according to this embodiment includes the following steps: S1. Epoxy polyester graft copolymer, ultrafine carbon black, organic solvent, near-infrared absorber and dispersant are added to a high-speed disperser and dispersed at 2000 rpm for 25 min. Then, the mixture is added to a grinder until the fineness is less than 5 μm. After adding curing agent and curing accelerator, the mixture is stirred at 800 rpm for 25 min. Finally, the mixture is degassed under a vacuum of -0.09 MPa for 25 min to obtain the ink. S2. The ink is slit extruded and coated onto the surface of the substrate layer at a coating speed of 40m / min and a coating thickness of 50μm. The temperature is raised to 75℃ for evaporation and drying for 180s, then raised to 115℃ for pre-curing for 180s, and finally raised to 180℃ for cross-linking and curing for 120s to obtain the heat-insulating ink coating. S3. Epoxy polyester graft copolymer, modified matte carbon black, fumed silica and organic solvent are added to a high-speed disperser and dispersed at 2000 rpm for 25 min. Latent curing agent and curing accelerator are added and stirred at low speed at 800 rpm for 25 min to obtain a spray coating. The spray coating is applied to the surface of the heat-insulating ink coating by air spraying. The spray gun nozzle diameter is 2 mm, the spraying pressure is 0.5 MPa, the spraying distance is 25 cm, the gun speed is 0.8 m / s, and three coats are applied. The thickness of each coat is 4 μm. The spraying interval is as follows: heat up to 60℃ for flash evaporation for 60 s, heat up to 75℃ for evaporation and drying for 120 s, heat up to 115℃ for pre-curing for 90 s, and finally heat up to 180℃ for cross-linking and curing for 150 s. Cool to room temperature to obtain a micro-nano rough layer. S4. Cool the cured light-shielding film to room temperature, roll it up at a speed of 30m / min, cure it at 45℃ for 36h, and then cut and package it to obtain a high-temperature resistant, low-reflection lidar light-shielding film.
[0043] Example 3: A high-temperature resistant, low-reflection lidar light-shielding film of this embodiment includes, from bottom to top, a substrate layer, a heat-insulating ink coating, and a micro-nano roughening layer. The substrate layer is a polyimide film with a thickness of 80 μm; The heat-insulating ink coating is prepared from the following raw materials: 100g epoxy polyester graft copolymer, 15g ultrafine carbon black, 8g near-infrared absorber, 3g dispersant, 1.5g curing accelerator, 6g latent curing agent and 80g organic solvent; The micro-nano roughened layer is prepared from the following raw materials in parts by weight: 30g epoxy polyester graft copolymer, 8g modified matte carbon black, 4g fumed silica, 2g latent curing agent, 0.3g curing accelerator and 50g organic solvent.
[0044] The near-infrared absorber is prepared by mixing phthalocyanine near-infrared absorbing dye TIR-915 and diimide near-infrared absorber CIR-1080 in a mass ratio of 1:1.
[0045] The latent curing agent is dicyandiamide, and the curing accelerator is 2-methylimidazole.
[0046] The organic solvent is an organic solvent prepared by mixing butanone, cyclohexanone and propylene glycol methyl ether acetate in a volume ratio of 6:4:3.
[0047] The method for preparing modified matte carbon black in this embodiment includes the following steps: S11. Add 155 mL of ethanol and 35 mL of deionized water to a stirred tank. While stirring, add 5.5 mL of ammonia and 11 mL of tetraethyl orthosilicate. Stir at 35 °C and 650 rpm for 90 min to obtain a suspension. Then add 1.05 g of resorcinol and 1.5 mL of 37 wt% formaldehyde. Heat to 55 °C and react for 18 h. After the reaction is complete, centrifuge at 9000 rpm for 7.5 min to collect the solid. Wash with deionized water and ethanol in sequence, and dry at 55 °C for 9 h to obtain the carbon source precursor. S12. The carbon source precursor is added to a tube furnace and heated to 750°C at a heating rate of 4°C / min in a nitrogen atmosphere. The carbonization is carried out at 750°C for 3 hours. After carbonization, the carbonization product is cooled to room temperature in a nitrogen atmosphere. The carbonized product is then added to 500 mL of an 85 g / L sodium hydroxide aqueous solution for etching for 42 hours to remove silicon dioxide. The solid is collected by filtration, washed with deionized water and ethanol in sequence, and dried at 55°C for 9 hours to obtain hollow carbon spheres. S13. Weigh 4.5g of hollow carbon spheres and add them to 165mL of deionized water. Add 3.65g of zinc acetate, 1.25g of malic acid and 35mL of isopropanol and stir to mix. Then add 11mL of sodium hydroxide aqueous solution with a concentration of 40g / L. Transfer the mixture to a closed hydrothermal reactor and heat it to 118℃ for hydrothermal reaction for 5h. After the reaction is completed, cool it to room temperature, filter and collect the solid, wash it with deionized water, dry it at 55℃ for 9h, and then heat the obtained solid to 375℃ at a heating rate of 2.5℃ / min. Anneal it at 375℃ for 1.5h and cool it to room temperature to obtain modified matte carbon black.
[0048] The preparation method of the epoxy polyester graft copolymer in this embodiment includes the following steps: S21. Add 18g neopentyl glycol, 3g 1,3-propanediol and 1g trimethylolpropane to a reaction vessel and heat to 100℃. Stir and mix at 100rpm for 30min. Add 25g terephthalic acid and 3g 1,4-cyclohexanedicarboxylic acid under a nitrogen atmosphere. Add 0.1g toluenesulfonic acid to catalyze the reaction. Heat to 180℃ for esterification for 6h. Then heat to 240℃ for esterification for 4h. React until no more water is distilled off. Evacuate to -0.09MPa and polycondense at 210℃ for 4h. Cool to 200℃ and add 6g trimellitic anhydride. Keep the reaction at 200℃ for 60min. The acid value is 30mgKOH / g. Cool to 180℃ and discharge to obtain carboxyl-terminated polyester resin. S22. Add 30g of epoxy resin E-51 and 70g of carboxyl-terminated polyester resin to a reactor, heat to 110℃ and stir at 80rpm for 30min, add 0.1g of triphenylphosphine, heat to 160℃ in a nitrogen atmosphere and react for 4h. When the acid value is 4mgKOH / g, the reaction ends, cool to 90℃ and discharge to obtain epoxy polyester graft copolymer.
[0049] The method for preparing a high-temperature resistant, low-reflection lidar light-shielding film according to this embodiment includes the following steps: S1. Epoxy polyester graft copolymer, ultrafine carbon black, organic solvent, near-infrared absorber and dispersant are added to a high-speed disperser and dispersed at 2500 rpm for 30 min. Then, the mixture is added to a grinder until the fineness is less than 5 μm. After adding curing agent and curing accelerator, the mixture is stirred at 600 rpm for 30 min. Finally, the mixture is degassed under a vacuum of -0.08 MPa for 40 min to obtain the ink. S2. The ink is slit extruded and coated onto the surface of the substrate layer at a coating speed of 50 m / min and a coating thickness of 15 μm. The temperature is raised to 75℃ for evaporation and drying for 60 s, then raised to 125℃ for pre-curing for 180 s, and finally raised to 200℃ for cross-linking and curing for 200 s to obtain the heat-insulating ink coating. S3. Epoxy polyester graft copolymer, modified matte carbon black, fumed silica and organic solvent are added to a high-speed disperser and dispersed at 2500 rpm for 30 min. Latent curing agent and curing accelerator are added and stirred at 600 rpm for 30 min to obtain a spray coating. The spray coating is then applied to the surface of the heat-insulating ink coating by air spraying. The spray gun nozzle diameter is 2.5 mm, the spraying pressure is 0.5 MPa, the spraying distance is 20 cm, the gun speed is 0.9 m / s, and two coats are applied. The thickness of each coat is 5 μm. The spraying interval is as follows: heat to 60℃ for flash evaporation for 30 s, heat to 85℃ for evaporation and drying for 60 s, heat to 125℃ for pre-curing for 60 s, and finally heat to 200℃ for cross-linking and curing for 100 s. The coating is then cooled to room temperature to obtain a micro-nano rough layer. S4. Cool the cured light-shielding film to room temperature, roll it up at a speed of 20m / min, cure it at 40℃ for 36h, and then cut and package it to obtain a high-temperature resistant, low-reflection lidar light-shielding film.
[0050] Comparative Example 1 differs from the Examples in that the polyimide film is replaced with a polyethylene terephthalate film.
[0051] Comparative Example 2 differs from the Examples in that an epoxy-polyester graft copolymer is used instead of ordinary bisphenol A epoxy resin E-44 and carboxyl-terminated polyester resin obtained by physical blending at a mass ratio of 65:35.
[0052] Comparative Example 3 differs from the embodiment in that the micro-nano rough layer is applied to the surface of the heat-insulating ink coating by slit extrusion coating at a speed of 30 m / min and a coating thickness of 10 μm.
[0053] Performance testing According to GB / T 25968-2010 "Spectrophotometer Test Method for Measuring Solar Transmittance and Solar Absorbance of Materials", a standard white board was used as the reflection reference. A CIE standard light source D65 was used for perpendicular incidence. A spectrophotometer with a spectral range of 0.3~2.5μm was used to scan the reflectance of the light-shielding films prepared in each embodiment and comparative example relative to the standard white board. The reflectance of the light-shielding films prepared in each embodiment and comparative example at two wavelengths of 905nm and 1550nm was extracted from the measured spectral reflectance data. Each light-shielding film was measured 3 times and the average value was taken.
[0054] According to GB / T 25968-2010 "Test Method for Measuring Solar Transmittance and Solar Absorbance of Materials by Spectrophotometer", the standard solar spectral radiation data with atmospheric mass AM1.5 was used for weighted integration. Air was used as a reference for 100% transmission baseline calibration. A CIE standard light source (D65) was used for perpendicular incidence. The spectral transmittance of the light-shielding films prepared in each embodiment and comparative example was measured and recorded using a spectrophotometer in the range of 380–780 nm, with measurement intervals of 5 nm. The visible light optical density (OD) value was calculated. The formula for calculating the optical density is shown below:
[0055]
[0056] τ v Visible light transmittance; Δλ is the wavelength interval, in nm; τ(λ) is the spectral transmittance; V(λ) is the CIE human visual spectral response function; D λThe relative spectral power distribution of the CIE standard light source D65 at wavelength λ; OD stands for optical density.
[0057] According to GB / T 9286-2021 "Cross-cut test for paints and varnishes", the adhesion of the light-shielding films prepared in each example and comparative example was measured. A 6×6 grid with a spacing of 1 mm was cut on the coating surface using a multi-blade cross-cut knife. 610 standard pressure-sensitive tape was applied to the grid area and peeled off smoothly at a 60° angle for 1 second. The peeling of the coating in the grid area was observed.
[0058] The light-shielding films prepared in each embodiment and comparative example were placed in an oven and heated at 260°C for 30 minutes. The film surface was observed. The film surface was then subjected to damp heat aging at 85°C and 85% relative humidity for 1000 hours. The reflectance at a wavelength of 905nm was also measured.
[0059] The test results are shown in Table 1 below: Table 1 Test Results
[0060] As shown in Table 1, the light-shielding films prepared in Examples 1-3 have a reflectance of 1.21-1.29% at 905nm, a reflectance of 1.60-1.68% at 1550nm, and an OD of 4.3. This indicates that the light-shielding films prepared in this invention have excellent light-shielding performance in the visible light band. The introduction of near-infrared absorbers produces characteristic absorption at 905nm and 1550nm, compensating for the reduced absorption capacity of carbon black in the near-infrared region. This effectively suppresses light interference in the near-infrared band. The micro-nano roughened layer in Comparative Example 3 was prepared by slit extrusion coating, which could not form a micro-nano roughened surface, resulting in a decrease in its light-harvesting ability. Its reflectance at 905nm was 3.55%, its reflectance at 1550nm was 4.21%, and its OD was 4.2, further demonstrating that the light-shielding films prepared in this invention have excellent low reflectance. The adhesion rating of the light-shielding films prepared in Examples 1-3 is 5B. They were subjected to humid heat aging at 85°C and 85% relative humidity. After 1000 hours of damp heat aging test, the coating appearance remained unchanged, and the reflectance at 905 nm increased by less than 0.3%, indicating that the light-shielding film prepared by the present invention has excellent resistance to damp heat aging. The resin prepared in Comparative Example 2 was only a physical blend of epoxy resin and carboxyl-terminated polyester resin. After 1000 hours of damp heat aging at 85°C and 85% relative humidity, the reflectance at 905 nm increased to 3.8%, indicating that the epoxy-polyester graft copolymer formed by the physical entanglement of epoxy self-crosslinking network and polyester chain segments can improve the resistance to damp heat aging of the light-shielding film. The light-shielding films prepared in Examples 1-3 showed no shrinkage, blistering, or cracking when heated at 260°C for 30 minutes. When the polyimide film in Comparative Example 1 was replaced with a polyethylene terephthalate film, the film shrank and deformed severely after being heated at 260°C for 30 minutes, indicating that the light-shielding film prepared by the present invention using polyimide film as the substrate layer has excellent heat resistance.
[0061] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0062] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-temperature resistant, low-reflection lidar light-shielding film, characterized in that, From bottom to top, it includes a substrate layer, a heat-insulating ink coating, and a micro-nano roughening layer; The substrate layer is a polyimide film with a thickness of 20~100μm; The heat-insulating ink coating is prepared from the following raw materials in parts by weight: 100 parts epoxy polyester graft copolymer, 10-15 parts ultrafine carbon black, 3-8 parts near-infrared absorber, 1-3 parts dispersant, 0.5-1.5 parts curing accelerator, 3-6 parts latent curing agent and 50-80 parts organic solvent; The micro-nano roughened layer is prepared from the following raw materials in parts by weight: 20-30 parts epoxy polyester graft copolymer, 5-8 parts modified matte carbon black, 3-5 parts fumed silica, 1-2 parts latent curing agent, 0.1-0.3 parts curing accelerator and 30-50 parts organic solvent.
2. The high-temperature resistant, low-reflection lidar light-shielding film according to claim 1, characterized in that, The near-infrared absorber is at least one of phthalocyanine near-infrared absorbing dyes or diimine near-infrared absorbers; the latent curing agent is dicyandiamide; the curing accelerator is 2-methylimidazole; the organic solvent is an organic solvent prepared by mixing butanone, cyclohexanone and propylene glycol methyl ether acetate in a volume ratio of 4~6:2~4:1~3; the average particle size of the ultrafine carbon black is 20~30nm, and the oil absorption value is 90~100mL / 100g.
3. The high-temperature resistant, low-reflection lidar light-shielding film according to claim 1, characterized in that, The preparation method of the modified matte carbon black includes the following steps: S11. Add ethanol and deionized water to a stirred tank, add ammonia and tetraethyl orthosilicate under stirring to prepare a suspension, then add resorcinol and 37wt% formaldehyde, heat to hydrothermal reaction, centrifuge and filter to collect the solid, wash with deionized water and ethanol in sequence, dry to obtain carbon source precursor. S12. The carbon source precursor is added to a tube furnace and carbonized in a nitrogen atmosphere. After cooling to room temperature, it is added to an 80-90 g / L sodium hydroxide aqueous solution to etch away silicon dioxide. The solid is collected by filtration, washed with deionized water and ethanol in sequence, and dried to obtain hollow carbon spheres. S13. Hollow carbon spheres are added to deionized water, zinc acetate, malic acid and isopropanol are added and stirred, 40 g / L sodium hydroxide aqueous solution is added, the mixture is heated and reacted, the solid is collected by filtration, washed with deionized water, dried, annealed and cooled to room temperature to obtain modified matte carbon black.
4. The high-temperature resistant, low-reflection lidar light-shielding film according to claim 3, characterized in that, Preferably, in S11, the ratio of ethanol, deionized water, ammonia, tetraethyl orthosilicate, resorcinol, and 37wt% formaldehyde is (150~160) mL : (30~40) mL : (5~6) mL : (10~12) mL : (0.8~1.3) g : (1.2~1.8) mL. The mixture is stirred at 500~800 rpm for 60~120 min at 30~40℃, then heated to 50~60℃ and reacted for 12~24 h. The mixture is then centrifuged at 8000~10000 rpm for 5~10 min and dried at 50~60℃ for 6~12 h. In S12, the mixture is heated to 700~800℃ at a heating rate of 3~5℃ / min for 2~4 h, etched with sodium hydroxide aqueous solution for 36~48 h, and dried at 50~60℃ for 6~12 h.
5. The high-temperature resistant, low-reflection lidar light-shielding film according to claim 3, characterized in that, The ratio of hollow carbon spheres, zinc acetate, malic acid, isopropanol, deionized water, and sodium hydroxide aqueous solution in S13 is (3~6) g : (3.5~3.8) g : (1~1.5) g : (30~40) mL : (160~170) mL : (10~12) mL. The mixture is heated to 115~120℃ for hydrothermal reaction for 4~6 h, dried at 50~60℃ for 6~12 h, and annealed at 350~400℃ for 1~2 h at a heating rate of 2~3℃ / min.
6. The high-temperature resistant, low-reflection lidar light-shielding film according to claim 1, characterized in that, The preparation method of the epoxy polyester graft copolymer includes the following steps: S21. Neopentyl glycol, 1,3-propanediol and trimethylolpropane are added to a reaction vessel and heated and stirred. Terephthalic acid and 1,4-cyclohexanedicarboxylic acid are added under a nitrogen atmosphere. Toluenesulfonic acid is added and heated to esterify. The reaction is continued until no more water is distilled off. Vacuum polycondensation is carried out. Trimeric trioxide is added after cooling. The reaction is maintained at the temperature. The acid value is tested. The material is discharged after cooling to obtain carboxyl-terminated polyester resin. S22. Epoxy resin and carboxyl-terminated polyester resin are added to a reactor, heated and stirred to mix, triphenylphosphine is added, and the mixture is heated and reacted in a nitrogen atmosphere. The acid value is detected, the mixture is cooled and discharged to obtain an epoxy polyester graft copolymer.
7. The high-temperature resistant, low-reflection lidar light-shielding film according to claim 6, characterized in that, In S21, the mass ratio of neopentyl glycol, 1,3-propanediol, trimethylolpropane, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, toluenesulfonic acid, and trimellitic anhydride is 18~22:3~5:1~1.5:25~30:3~5:0.1~0.3:6~10. The mixture is heated to 100~130℃ and stirred at 100~300 rpm for 10~30 minutes. The temperature is then raised to 18... Esterification at 0~220℃ for 4~6h, then esterification at 240~265℃ for 2~4h, vacuuming to -0.09~-0.1MPa, polycondensation at 210~215℃ for 1~4h, cooling to 200~205℃ and adding trimellitic anhydride, holding the reaction at 200~220℃ for 30~60min, detecting an acid value of 30~60mgKOH / g, and discharging at 180~190℃.
8. The high-temperature resistant, low-reflection lidar light-shielding film according to claim 6, characterized in that, The epoxy resin in S22 is any one of E-44, E-42, and E-51. The mass ratio of epoxy resin, carboxyl-terminated polyester resin, and triphenylphosphine is 30~40:60~70:0.1~0.
5. The mixture is heated to 110~130℃ and stirred at 80~100 rpm for 20~30 min. The mixture is then heated to 160~200℃ and reacted for 2~4 h. The reaction ends when the acid value is less than 5 mg KOH / g. The mixture is then cooled to below 100℃ and discharged.
9. A method for preparing a high-temperature resistant, low-reflection lidar light-shielding film according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Epoxy polyester graft copolymer, ultrafine carbon black, organic solvent, near-infrared absorber and dispersant are added to a high-speed disperser and stirred and dispersed. Then, they are added to a grinding mill and ground. After adding curing agent and curing accelerator, they are stirred and mixed at low speed. Vacuum degassing is performed to obtain ink. S2. The ink is slit-extruded and coated onto the surface of the substrate layer, and then heated and dried in stages to obtain a heat-insulating ink coating. S3. Epoxy polyester graft copolymer, modified matte carbon black, fumed silica and organic solvent are added to a high-speed disperser and stirred and dispersed. Latent curing agent and curing accelerator are added and stirred at low speed to obtain a spray coating. The spray coating is sprayed onto the surface of the heat insulation ink coating and heated and cured to obtain a micro-nano rough layer. S4. Cool the cured light-shielding film to room temperature, roll it up, cure it, cut and package it to obtain a high-temperature resistant, low-reflection lidar light-shielding film.
10. The method for preparing a high-temperature resistant, low-reflection lidar light-shielding film according to claim 9, characterized in that, In step S1, the mixture is dispersed at 1500-2500 rpm for 20-30 minutes, ground to a fineness of less than 5 μm, stirred at 500-800 rpm for 20-30 minutes, and degassed under a vacuum of -0.08 to -0.1 MPa for 20-40 minutes. In step S2, the coating speed is 10-50 m / min, the coating thickness is 15-60 μm, the temperature is raised to 75-85℃ for evaporation and drying for 60-180 seconds, then raised to 115-125℃ for pre-curing for 60-180 seconds, and finally raised to 180-200℃ for cross-linking and curing for 60-300 seconds. In step S3, the mixture is dispersed at 1500-2500 rpm for 20-30 minutes, and stirred at 500-800 rpm for 20-30 minutes. Stir for 20-30 minutes, degas under vacuum of -0.08 to -0.1 MPa for 20-40 minutes, and apply by air spraying with a nozzle diameter of 1.5-2.5 mm, a spraying pressure of 0.3-0.5 MPa, a spraying distance of 15-25 cm, and a gun speed of 0.5-1.0 m / s. Apply 2-3 coats, each with a thickness of 3-5 μm. During the spraying interval, raise the temperature to 60-65℃ for flash evaporation for 30-60 seconds, raise the temperature to 75-85℃ for evaporation and drying for 60-120 seconds, raise the temperature to 115-125℃ for pre-curing for 60-120 seconds, and finally raise the temperature to 180-200℃ for cross-linking and curing for 60-200 seconds. In step S4, the mixture is wound up at a rate of 20-50 m / min and cured at 40-50℃ for 24-48 hours.
Citation Information
Patent Citations
A lens shading film, a preparation method and application thereof
CN119861478B